Abortos de semillas de Enterolobium cyclocarpum (Mimosoideae): efecto de la posición relativa dentro del fruto - Villalobos, Federico (Universidad de Costa Rica, 2000)
We examined if seed abortion in Guanacaste tree fruits (Enteralobium cyclocarpum) is related to po sition within fruits, by establishing (he abortion ratio in 150 fruits from 10 trees, collected in Santa Rosa National Park (Guanacaste, Costa Rica). Fruits were divided in basal, central and distal sections. We found marginal differences in abortion ratio between these sections (Anova, p= 0.058), and also among trees (p= 0.01). In general, the distal section had the greatest abortion ratio in relation to other sections. This abortion pattem could be caused by resource competition within siblings and not by genetic differences among them.